Editorial - Poulakka, Kalle (The Nordic Journal of Aesthetics, 2011)
<!--StartFragment--> The growing amount of anthologies, monographs, and textbooks shows that environmental aesthetics is a discipline, which has indeed come of age. For a long time the discipline lay at the outskirts of philosophical aesthetics, but from the beginning of the 1960s interest in it began to grow rapidly, and it has now evolved into a respectable philosophical discipline with a specific set of core issues and interesting debates. The “Environment, Aesthetics, and the Arts” conference arranged in Lahti, Finland in June 2010, in co-operation by the Nordic Society of Aesthetics, the Finnish Society of Aesthetics, and the International Institute of Applied Aesthetics, was devoted to the latest developments in environmental aesthetics. And the papers presented at the conference reinforced the picture of environmental aesthetics as a legitimate part of philosophical aesthetics. This special issue of The Nordic Journal of Aesthetics collects <!--EndFragment-->